Molecular Characterization of Candida auris Isolates at a Major Tertiary Care Center in Lebanon - Reslan, Lina; Araj, George F.; Finianos, Marc; El Asmar, Rima; Hrabak, Jaroslav; Dbaibo, Ghassan; Bitar, Ibrahim (Frontiers in Microbiology, 2022)
Background: The globally emerging C. auris pathogens poses heavy burden to the healthcare system. Their molecular analyses assist in understanding their epidemiology, dissemination, treatment and control. This study was warranted to describe the genomic features and drug resistance profiles using whole genome sequencing (WGS) among C. auris isolates from Lebanon. Methods: A total of 28 C. auris clinical isolates, from different hospital units, were phenotypically identified by MALDI-TOF and tested for antifungal resistance using Vitek-2 system and E test. The complete genomes were determined by WGS using long reads sequencing (PacBio) to reveal the Clade distribution and antifungal resistance genes. Results: C. auris revealed uniform resistance to fluconazole and amphotericin B, with full susceptibility to echinocandins. Among key resistance genes studied, only two mutations were detected: Y132F in ERG11 gene and a novel mutation, D709E found in CDR1 gene encoding for an ABC efflux pump. Phylogenetically, C. auris genomes belonged to South Asian clade I and showed limited genetic diversity, suggesting person to person transmission. Conclusion This characterization of C. auris isolates from Lebanon revealed the exclusivity of clade I lineage together with uniform resistance to fluconazole and amphotericin B. The control of such highly resistant pathogen necessitates an appropriate and rapid recovery and identification to contain spread and outbreaks.